2017
DOI: 10.1186/s12966-017-0563-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a mobile app intervention on vegetable consumption in overweight adults: a randomized controlled trial

Abstract: BackgroundMobile applications (apps) have been heralded as transformative tools to deliver behavioral health interventions at scale, but few have been tested in rigorous randomized controlled trials. We tested the effect of a mobile app to increase vegetable consumption among overweight adults attempting weight loss maintenance.MethodsOverweight adults (n=135) aged 18–50 years with BMI=28–40 kg/m2 near Stanford, CA were recruited from an ongoing 12-month weight loss trial (parent trial) and randomly assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
68
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 33 publications
2
68
0
7
Order By: Relevance
“…Results of a previous review examining the effectiveness of text message intervention for youth align with those of this review, where the level of physical activity significantly improved (Ludwig, Arthur, Sculthorpe, Fountain, & Buchan, ). Additionally, previous research demonstrated the effects of implementing mobile phone intervention on dietary habits, such as increasing vegetable consumption (Elbert, Dijkstra, & Oenema, ; Mummah et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…Results of a previous review examining the effectiveness of text message intervention for youth align with those of this review, where the level of physical activity significantly improved (Ludwig, Arthur, Sculthorpe, Fountain, & Buchan, ). Additionally, previous research demonstrated the effects of implementing mobile phone intervention on dietary habits, such as increasing vegetable consumption (Elbert, Dijkstra, & Oenema, ; Mummah et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…The pilot study established the feasibility of sending text messages with information on a participant's own adherence and adherence performance relative to peers. Receipt of group information has been shown to effectively improve other health behaviors, such as increased physical activity [31][32][33] and improved food choices [33][34][35], as well as minimizing alcohol use [36] and improving sexual health [37,38]. Our pilot data suggests that it may also be used to improve ART adherence.…”
Section: Discussionmentioning
confidence: 87%
“…The pilot study established the feasibility of sending text messages with information on a participant's own adherence and adherence performance relative to peers. Receipt of group information has been shown to effectively improve other health behaviors, such as increased physical activity [30][31][32] and improved food choices [32][33][34], as well as minimizing alcohol use [35] and improving sexual health [36,37]. Our pilot data suggests that it may also be used to improve ART adherence.…”
Section: Discussionmentioning
confidence: 87%